Pembuatan Game Musical Puzzle “Music Puzzle” Pada Platform Android - Ewaldo Filbert; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
“Music Puzzle” is a musical puzzle game for Android. Player will try to arrange the puzzle piece by listening to the music in each puzzle and correct the order of the music. This game use classical music as the theme of the game. This game is developed by Unity game engine with C# as the programming language. Testing has been done with Black Box Testing, Alpha Testing by lecturer and Beta Testing by survey to 30 respondents. The results show that the “Music Puzzle” is an interesting game to play and encourage respondents to interest in classical music.